2013
DOI: 10.1093/carcin/bgt379
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin signaling enhances colon cancer stemness by modulating Notch signaling in a Jak2-STAT3/ERK manner

Abstract: Prolactin (PRL) is a secretory cytokine produced by various tissues. Binding to the cognate PRL receptor (PRLR), it activates intracellular signaling via janus kinase (JAK), extracellular signal-regulated kinase (ERK) and signal transducer and activator of transcription (STAT) proteins. PRL regulates diverse activities under normal and abnormal conditions, including malignancies. Previous clinical data suggest serum PRL levels are elevated in colorectal cancer (CRC) patients. In this study, we first determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 69 publications
2
44
1
Order By: Relevance
“…At first sight, these data may argue against the involvement of Hes3 downstream of FGF10 signaling because Hes3 activation may be expected to result in low Hes1 and high Pdx1, at least based on data from mouse insulinoma cell lines and the adult pancreata from Hes3-null mice (43). However, FGF10 signaling can also activate the JAK-STAT pathway, which is a strong inhibitor of Hes3 as well as an inducer of Hes1 in other immature cell types (110). Similarly, in NSC cultures, the cytokine ciliary neurotrophic factor can be converted from a prodifferentiation signal suppressing Hes3 transcription to a mitogen promoting Hes3 transcription simply by cotreatment with a JAK inhibitor (78).…”
Section: Integrating Fgf10 Signalingmentioning
confidence: 99%
“…At first sight, these data may argue against the involvement of Hes3 downstream of FGF10 signaling because Hes3 activation may be expected to result in low Hes1 and high Pdx1, at least based on data from mouse insulinoma cell lines and the adult pancreata from Hes3-null mice (43). However, FGF10 signaling can also activate the JAK-STAT pathway, which is a strong inhibitor of Hes3 as well as an inducer of Hes1 in other immature cell types (110). Similarly, in NSC cultures, the cytokine ciliary neurotrophic factor can be converted from a prodifferentiation signal suppressing Hes3 transcription to a mitogen promoting Hes3 transcription simply by cotreatment with a JAK inhibitor (78).…”
Section: Integrating Fgf10 Signalingmentioning
confidence: 99%
“…There is an association between PRL and its receptor's overexpression with the development of different types of cancer such as breast, laryngeal, prostate, colon and cervical cancer (22,23,(32)(33)(34)(35)(36). The role of circulating PRL in tumorigenesis, mainly in breast cancer, has been a topic of debate for more than 20 years since various epidemiological studies were unable to reach unified conclusions on the correlation between circulating PRL levels and risk for cancer (37,38).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, most of the 200 up-regulated genes in Sel1L-deficient cells are associated with either cell adhesion or proliferation. Gene set enrichment analysis showed that these genes overlap significantly with a group of so-called "Stemness" genes in the IL6/STAT3 signaling pathway [28,29]. While further studies are needed to ascertain whether the ERAD-deficient HepG2 cells have reverted to stem-like or more aggressive cells, these results provide evidence that ERAD deficiency may potentiate mammalian cells towards stem or cancer-like cells, perhaps through influencing their mitochondrial function.…”
Section: Discussionmentioning
confidence: 91%
“…As expected, genes of a reported mitochondrial gene module [27] were overrepresented in the down-regulated DEGs in ERAD-deficient HepG2 cells ( Fig 5B). Intriguingly, the Jak2 signaling pathway-associated or the so called 'stemness' genes [28,29] were highly represented in the up-regulated DEGs (Fig 5C). Together, these results indicate that ERAD deficiency caused a global reorganization of transcription that disrupts multiple mitochondrial activities and activates several pathways associated with the stemness or invasiveness property of eukaryotic cells.…”
Section: Erad Deficiency Causes Transcriptional Rewiring That Disruptmentioning
confidence: 98%